Kelor Leaf Extraction As Organic Inhibitor Of Steel In Seawater Training To Increase Competence Luqman Al-Hakim Surabaya High School Teachers And Students. - Tubagus Noor Rohmannudin; Agung Purniawan; Moh. Farid; Fakhreza Abdul; Zaid Sulaiman; Sulistijono Sulistijono (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2020)
The Materials Engineering Department held the training as a public service program with participants coming from Teachers and Students of Luqman Al-Hakim Surabaya High School. This training was held at the Materials Engineering Department. The training method used was the presentation of material by the Team, followed by experiments in the Laboratory. These results indicate an increase in the competency, insight and understanding of Luqman Al-Hakim High School Teachers and Students regarding the process of Kelor leaves as an organic inhibitor.